The Awareness of Population about Ionizing Radiation: Lithuanian Mass Media Content Variety Analysis - Sprudzanaitė, Ausma; Austys, Donatas (Žurnalistikos tyrimai, 2025)
Background. Mass media have an important role in shaping the public information field. In times of crises, mass media acts as a mediator which could deliver expert knowledge to society. Challenging the current geopolitical situation emphasized the mass media importance. Therefore, the aim of this study is to assess the thematic content variety of information related to radiation safety in Lithuanian mass media. Methods. A qualitative content analysis of 322 mass media publications was conducted, while focusing on sources of ionizing radiation, health effects of ionizing radiation, radiation safety measures, and public preparedness in the context of a nuclear accident or war. Publications from the mass media portals delfi.lt, 15min and lrt.lt were included in this content analysis. Results. More than half of the publications (61.8%) mention sources of ionizing radiation found in the air. The majority of those (66.5%) are associated with nuclear energy. Sources of ionizing radiation used in soil, water, food and medicine are mentioned in 6.8%, 14.6%, 4.0% and 5.9% of the publications, respectively. Additionally, more than half (59.0%) of the publications mention radiation safety, and one third (32.3%) mentions nuclear accident preparedness. The topics of the health effects of ionizing radiation, radiation safety measures and nuclear accident preparedness are discussed with a similar frequency in lrt.lt, 15min.lt and delfi.lt mass media portals. (p>0.05). Conclusions. Although the largest Lithuanian mass media portals provide a variety of information about ionizing radiation, effects on health, radiation safety and nuclear accident preparedness, a thematic imbalance is observed as airborne sources of ionizing radiation are mentioned more often than others. In some publications, (over)dramatization of content is observed, which may cause anxiety or panic in society.